2015
DOI: 10.17795/nmsjournal24320
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Violence in the Health Care Settings in Iran: A Cross-Sectional Study

Abstract: Background: Psychological violence is the most common form of workplace violence that can affect professional performance and job satisfaction of health care workers. Although several studies have been conducted in Iran, but there is no consensus regarding current status of such violence. Objectives: This study aimed to investigate the prevalence of psychological violence among healthcare workers employed at teaching hospitals in Iran. Patients and Methods:In this cross-sectional study, 5874 health professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
3
24
1
1
Order By: Relevance
“…The findings of quantitative research conducted in Iran suggest that it is possible to compare the frequency of violence in Iran with the frequency of violence observed in international studies (Esmaeilpour, Salsali, & Ahmadi, ; Fallahi‐Khoshknab, Oskouie, Najafi et al., ; Fallahi‐Khoshknab, Oskouie, Najafi et al, ). The Iranian research found that the frequency of violence in psychiatric units was 71% (Fallahi‐Khoshknab, Tamizi, Ghazanfari, & Mehrabani, ) and that the frequencies of sexual and racial harassment were 4.7% and 12%, respectively (Fallahi‐Khoshknab, Oskouie, Ghazanfari et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of quantitative research conducted in Iran suggest that it is possible to compare the frequency of violence in Iran with the frequency of violence observed in international studies (Esmaeilpour, Salsali, & Ahmadi, ; Fallahi‐Khoshknab, Oskouie, Najafi et al., ; Fallahi‐Khoshknab, Oskouie, Najafi et al, ). The Iranian research found that the frequency of violence in psychiatric units was 71% (Fallahi‐Khoshknab, Tamizi, Ghazanfari, & Mehrabani, ) and that the frequencies of sexual and racial harassment were 4.7% and 12%, respectively (Fallahi‐Khoshknab, Oskouie, Ghazanfari et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the minority of disruptive behaviors can have a huge effect on productivity, performance, and staff behavior in an organization, it seems essential to conduct a study that reflects the perspective and experiences of nurses who are perpetrators or targeted in disruptive behaviors. Because most studies in this field focusing on the prevalence and type of behaviors and its consequences and determined individual, organizational, environmental, and social factors have been as causes of these behaviors 3,19 but how these factors play a role in this accident has not been fully explored. So maybe the qualitative nature of this study and its data collection methods could provide new attitudes that may lead to create effective strategies for reducing the incidence and malicious consequences of these behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…3 En un estudio reciente en Irán, de una muestra al azar de más de 5000 trabajadores de la salud, se observó que un 74% había padecido algún grado de agresión psicológica en el último año. 18 En Egipto, un estudio que incluyó enfermeras del área perinatal de 8 hospitales encontró que el 86% había experimentado algún episodio de violencia en los últimos 6 meses y que un tercio había sido de tipo físico. 5 En España, un estudio del año 2009 mostró que un 11% de los trabajadores de la salud había sido víctima de una agresión física y un 64% había recibido amenazas, intimidación o insultos.…”
Section: Discussionunclassified